Interventions to Decrease Inappropriate Antibiotic Use for Non-acute Respiratory Illness in Long-Term Care Settings (International Journal of Studies in Nursing, 2019)
Background: The life-saving power of antibiotics could be lost forever if leaders fail to implement effective antibiotic stewardship programs at all healthcare levels. Grahams’ Knowledge to Action theory guided the development of an antibiotic stewardship program in a long-term care facility that had received a citation for having no active antibiotic stewardship program as required by federal regulations. Purpose: The purpose of this project was to develop and implement an evidence-based antibiotic stewardship program into one long-term care facility. Methods and Materials: This quality improvement project was a population-based systems charter development. The implementation intervention was designed to change the way health care professionals treat non-acute episodes of upper respiratory infections in a long-term care setting. This project utilized the suspected lower respiratory infection (LRI) Situation, Background, Assessment, Recommendation (SBAR) form to reduce the number of antibiotics given during the early part of cold and influenza season of 2018. An antibiotic stewardship policy was developed by multidisciplinary team members and then implemented into the facilities daily practice. Results: The point-prevalence rate of antibiotics within this facility dropped from 24% in 2017 to 6% in 2018 after implementation of the antibiotic stewardship program. Conclusion: This project demonstrates how long-term care facilities can successfully implement an antibiotic stewardship program and potentially improve overall healthcare outcomes for the residents.